2007
DOI: 10.1038/sj.bjp.0707179
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the expression of soluble guanylyl cyclase by reactive oxygen species

Abstract: Background and purpose: Superoxide anions produced during vascular disease scavenge nitric oxide (NO), thereby reducing its biological activity. The aim of the present study was to investigate whether reactive oxygen species (ROS) have a direct effect on soluble guanylyl cyclase (sGC) subunit levels and function and to ascertain the mechanism(s) involved. Experimental approach: Rat aortic smooth muscle cells (RASM) or freshly isolated vessels were exposed to reactive oxygen species (ROS)-generating agents and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 33 publications
5
34
0
Order By: Relevance
“…More recently, it was shown that rat aortic smooth muscle cells exposed to elevated levels of H 2 O 2 (500 mol/liter) for 24 h demonstrated decreased GC ␣ 1 -and ␤ 1 -subunit mRNA and protein expression; however, exposure to this concentration of H 2 O 2 was associated with a 25% decrease in cell viability. In addition, when these investigators exposed cells to a lower concentration of H 2 O 2 (150 mol/ liter), they saw no change in ␣ 1 -subunit protein expression and an increase in ␤ 1 -subunit expression (39). In our experiments, the levels of H 2 O 2 generated by aldosterone were similar to the lower concentration of H 2 O 2 studied by these investigators, and aldosterone treatment at these concentrations did not influence cell viability.…”
Section: Discussionsupporting
confidence: 60%
“…More recently, it was shown that rat aortic smooth muscle cells exposed to elevated levels of H 2 O 2 (500 mol/liter) for 24 h demonstrated decreased GC ␣ 1 -and ␤ 1 -subunit mRNA and protein expression; however, exposure to this concentration of H 2 O 2 was associated with a 25% decrease in cell viability. In addition, when these investigators exposed cells to a lower concentration of H 2 O 2 (150 mol/ liter), they saw no change in ␣ 1 -subunit protein expression and an increase in ␤ 1 -subunit expression (39). In our experiments, the levels of H 2 O 2 generated by aldosterone were similar to the lower concentration of H 2 O 2 studied by these investigators, and aldosterone treatment at these concentrations did not influence cell viability.…”
Section: Discussionsupporting
confidence: 60%
“…However, it is also important to remember that more prolonged exposure to reactive oxygen species leads to downregulation of sGC expression. Gerassimou et al have confirmed that sGC expression is reduced in freshly isolated rat aortic strips by exposure to superoxide-generating agents or hydrogen peroxide for a long period (23). In any case, taken together, the response to agents activating the reduced sGC would be diminished sooner or later if the generation of reactive oxygen and nitrogen species was stimulated.…”
Section: Discussionmentioning
confidence: 60%
“…The report by Wu and de Champlain has noted an inhibitory effect of superoxide on cGMP formation in vascular smooth muscle cells (24). Other investigators have also reported that exposure of smooth muscle cells to superoxide generating agents causes a decrease in sGC expression and attenuates cGMP formation induced by NO donors (25). In addition, NO-donors used in this study require enzymatic catalysis by mitochondrial aldehyde dehydrogenase 2 (ALDH2) or by P450 in the endoplasmic reticulum to release NO (26).…”
Section: Discussionmentioning
confidence: 82%